สตรีกับการเปนผูนำ - วังถนอมศักดิ์ มัทนา (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
สิ่งหนึ่งที่ปฏิเสธไมไดเลยนั่นคือ บทบาทของผูหญิงที่เพิ่มมากขึ้นในปจจุบัน ไมวาจะเปนทางสังคม การเมือง การปกครอง แตแมวาบทบาทของผูหญิงจะไดรับการยอมรับมากขึ้น หากแตในสังคมก็ยังมีปญหาเรื่องความไมเทาเทียมอยูดี ในบทความนี้ไดอธิบายถึงความแตกตางระหวางเพศหญิงและเพศชาย รวมถึงแนวทางการสงเสริมภาวะผูนำใหกับผูหญิงในปจจุบันดวย WOMEN AND LEADERSHIP One thing that cannot be denied is that female role is becoming more and more renowned socially and politically. Even though female roles are more notable, there are still problems of inequality. This article aimed to explain the differences between male and female, and also some clues in to helping today women achieve their leadership goals.